Two-phase SPH–FD depth-integrated model for debris flows: application to basal grid brakes. Issue 12 (4th November 2021) - Tayyebi, Saeid Moussavi; Pastor, Manuel; Yifru, Ashenafi Lulseged; Thakur, Vikas K. S.; Stickle, Miguel Martin
Abstract : In some cases, debris flow consists of low-permeability soils in which run-out distances, velocities and lateral spreading are highly influenced by pore-water pressures. Basal screens are energy dissipation structures designed to reduce these velocities and run-out distances. These structures consist of grids built on horizontal decks where basal pore pressures of debris flows are made equal to the atmospheric pressure, which increases basal friction. Once the debris flows exit the structure, basal pore pressure increases as the basal surface is impermeable again, but the values have been reduced. In order to model these phenomena, it is necessary to use debris flow simulation models considering two phases and pore-water pressures. Here, a depth-integrated two-phase smooth particle hydrodynamics (SPH) model, previously developed by the authors, is improved by including the vertical structure of pore-water pressure. This is done by incorporating finite-differences meshes associated to each SPH node that represents a solid particle. In this way, a higher precision is obtained in describing excess pore pressure along depth, including the influence of vertical consolidation, height variation and changes in basal permeability. The proposed model is applied to describe debris flows with two different ranges of soil permeability propagating over grid structures. The authors have used laboratory tests run at the Norwegian University of Science and Technology and studied the efficiency of the basal grids by comparing cases equipped by them and cases without any obstacle. The results obtained from the proposed numerical experiments suggest that the proposed two-phase coupled model is able to properly reproduce the behaviour of debris flows, describing more accurately the time–space evolution of pore-water pressures during the whole propagation stage, considering both propagation impermeable beds and pore pressure dissipation structures such as grids.